2015
DOI: 10.1186/s12879-016-1388-3
|View full text |Cite
|
Sign up to set email alerts
|

Young male sex workers are at high risk for sexually transmitted infections, a cross-sectional study from Dutch STI clinics, the Netherlands, 2006–2012

Abstract: BackgroundMale sex workers (MSW) are particularly exposed to sexually transmitted infections (STI) including HIV. In the Netherlands, data about STI among MSW are scarce. We estimated chlamydia, gonorrhoea, syphilis and HIV diagnoses among MSW attending STI clinics and determined associated factors to guide prevention policies.MethodsUsing 2006–2012 cross-sectional national surveillance data from Dutch STI clinics, we calculated the proportion of consultations with a positive test for any of three bacterial ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 23 publications
4
21
2
2
Order By: Relevance
“…As such, these populations may face greater exposure to STIs and health risks. These findings are consistent with Fournet et al (2016), which finds that young male sex workers who identify as bisexual or gay have a high risk of exposure to STIs.…”
Section: Discussionsupporting
confidence: 91%
“…As such, these populations may face greater exposure to STIs and health risks. These findings are consistent with Fournet et al (2016), which finds that young male sex workers who identify as bisexual or gay have a high risk of exposure to STIs.…”
Section: Discussionsupporting
confidence: 91%
“…Male sex workers (MSWs) in Europe report injecting drugs significantly longer than other men who inject drugs, with a higher proportion sharing needles (23% vs. 14%), and MSWs reported incarceration at a significantly younger age than their non-sex worker counterparts [37]. In the Netherlands, younger men were more than twice as likely to test positive for STBBIs, and identifying as gay or bisexual significantly increased risk [22].…”
Section: Resultsmentioning
confidence: 99%
“…Among the limited available data among MSWs, research from the UK found that rates of both unprotected sex and gonorrhoea both increased steadily over the study period (1994–2003) [21]. Among MSWs in the Netherlands, the rate of STIs (syphilis, chlamydia, gonorrhoea) increased from 15.2 to 21.1% between 2006 and 2010 and then dropped to 18.3% in 2012 [22].…”
Section: Resultsmentioning
confidence: 99%
“…Among Dutch blood donations that were screened for transfusion-transmissible infections from 1995 to 2014, the prevalence of syphilis increased by 50% from the period of 1995 to 2002 (22.3 positive tests per 100,000 new donors) to 2003 to 2014 (32.8 positive tests per 100,000 new donors) [131]. Among 3,052 consultations for male sex workers in Dutch STI clinics from 2006 to 2012, 2.6% of male sex workers tested positive for syphilis, with no significant change in prevalence throughout the study [132]. Among 36,296 consultations for female sex workers from 2006 to 2013, the syphilis positivity rate decreased from 0.6% in 2006 to 0.1% in 2013 [133].…”
Section: Introductionmentioning
confidence: 99%